Pemanfaatan Platform Edpuzzle dalam Pembelajaran Matematika - Adib Rozan; Sri Hastuti Rhomawati; Melati br Pasaribu (Konstanta : Jurnal Matematika dan Ilmu Pengetahuan Alam, 2024)
The shift from face-to-face learning to online and blended learning due to the Covid-19 pandemic presents challenges for educators and prospective teachers in designing effective instruction. One of the commonly used instructional media in online and blended learning is video. However, using video as a material delivery tool has its drawbacks, such as difficulties in monitoring student activities and assessing their understanding. This issue is also experienced by students of the Mathematics Study Program at Universitas PGRI Mahadewa Indonesia when using video as learning material. To address this problem, training was conducted for prospective teachers on designing instruction using videos integrated with the Edpuzzle platform. In this training, prospective teachers were taught to create notes and quizzes within videos, provide feedback and assessments, and monitor learning activities. Through this training, it is expected that prospective teachers can design interactive online and blended learning using video.